Sosialisasi Akuntansi dan Pelaporan Keuangan - Suparmin; Satiman; Edon Ramdani (Universitas Pamulang, 2025)
Accounting and Financial Reporting Awareness Program. In carrying out its activities, a company requires a function that plays an important role in safeguarding financial transactions, recording, and compiling economic events that have occurred, which are then documented in the form of journals, ledgers, and financial statements. Properly and accurately presented financial statements are essential for every company and organization.The application of accounting and financial reporting knowledge today is not limited to companies alone; individuals also need a sound understanding of accounting recording and reporting. One example is that understanding and knowledge of accounting have become important for senior high school students as preparation for pursuing higher education after graduation as well as for personal development. Based on this background, we, the team of lecturers from the Bachelor’s Program in Accounting and Management at Universitas Pamulang, took the initiative to share knowledge through a community service activity (PKM) aimed at providing benefits in the form of basic accounting knowledge and skills.The PKM team from Universitas Pamulang proposes to hold basic accounting training as an extracurricular activity for 12th-grade students at Yayasan Al Kamilah, located in Bojongsari, Depok, West Java. This activity is planned to be held on Monday, April 28, 2025, conducted offline at the school premises on Jl. Serua Raya, Bojongsari District, Depok City, West Java 16517. The main objective of this community service activity is to assist Yayasan Al Kamilah in improving the students’ literacy and understanding of basic accounting principles, thereby broadening their insight and knowledge of accounting. Overall, this PKM activity is expected to provide participants with an understanding of the importance of accounting knowledge and its application in daily life. The results of this PKM will be compiled into an article to be published in a nationally accredited journal, thereby enriching the body of knowledge and serving as a reference source for its readers. Keywords: Accounting; Financial Statements; Community Service; Lecturers; Students